LEGITIMASI HUKUM ADAT BALI DALAM KARYA SASTRA KULTURAL - I Kadek Adhi Dwipayana; Ida Bagus Gede Bawa Adnyana (Universitas Negeri Makassar, 2019)
Legitimacy of Balinese Customary Lawin Cultural Literature Works. This article talks about the legitimacy of Balinese customary law and the reinterpretation of the authors of Balinese customary law in cultural literary works. The source of research data comes from the collection of